Patient beliefs that chemotherapy may be curative and care received at the end of life among patients with metastatic lung and colorectal cancer. Issue 11 (11th February 2015) - Mack, Jennifer W.; Walling, Anne; Dy, Sydney; Antonio, Anna Liza M.; Adams, John; Keating, Nancy L.; Tisnado, Diana
<x xml:space="preserve">Abstract</x> BACKGROUND Many patients with incurable cancer inaccurately believe that chemotherapy may cure them. Little is known about how such beliefs affect choices for care at the end of life. This study assessed whether patients with advanced cancer who believed that chemotherapy might offer a cure were more likely to receive chemotherapy in the last month of life and less likely to enroll in hospice care before death. METHODS This study examined patients diagnosed with stage IV lung or colorectal cancer in the Cancer Care Outcomes Research and Surveillance consortium, a population‐ and health system–based prospective cohort study. Among 722 patients who completed a baseline survey and died during the study period, logistic regression was used to assess the association of understanding goals of chemotherapy with chemotherapy use in the last month of life and hospice enrollment before death; adjustments were made for patient and tumor characteristics. RESULTS One‐third of the patients (33%) recognized that chemotherapy was "not at all" likely to cure their cancer. After adjustments, such patients were no less likely than other patients to receive end‐of‐life chemotherapy (odds ratio [OR], 1.32; 95% confidence interval [CI], 0.84‐2.09), but they were more likely than other patients to enroll in hospice (OR, 1.97; 95% CI, 1.37‐2.82). CONCLUSIONS An understanding of the purpose of chemotherapy for incurable cancer is a critical aspect of informed consent. Still, advanced cancer patients who were well informed about chemotherapy's goals received late‐life chemotherapy at rates similar to those for other patients. An understanding of the incurable nature of cancer, however, is associated with increased hospice enrollment before death, and this suggests important care outcomes beyond chemotherapy use. Cancer 2015;121:1891–1897. © 2015 American Cancer Society.